STRATEGI PRODUK UNTUK MENGATASI HAMBATAN EKSPOR UKM INDUSTRI KERAJINAN INDONESIA - WIJAYA ADIDARMA (Program Studi Magister Manajemen FE Unsri, 2015)
Research in exporting has been devoted attention to examine problems related to exporting. However, few studies have been carried out to explore the export barriers of SMEs in Indonesia. This study examines the relationship between export barrier, product strategy and export performance. In this research, product strategy consists of product adaptation strategy, product quality strategy, and product innovation strategy. Results indicate that only product barriers positively influence product quality strategy. Law or regulation barriers unexpectedly influence product adaptation strategy negatively. This study also found the negative impact of customer barrier on product quality. None of other export barriers significantly influence product strategy. Meanwhile, unexpectedly none of those three-product strategies influence export performances.Keywords: export barriers, product adaptation, product quality, product innovation, export performance, small- and medium-enterprise, handicraft industry